2017
DOI: 10.1080/00461520.2017.1341319
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Epistemic Cognition in the Context of Dialogic Practice: A Question of Calibration?

Abstract: In this article, we argue that teachers' epistemic cognition, in particular their thinking about epistemic aims and reliable processes for achieving those aims, may impact students' understanding of complex, controversial issues. This is because teachers' epistemic cognition may facilitate or constrain their implementation of instruction aiming to engage students in reasoned argumentation through classroom dialogue. We also suggest that teachers may need to reflect on their own epistemic cognition in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 88 publications
0
11
0
1
Order By: Relevance
“…Moreover, several researchers have studied argumentative reasoning about multiple perspectives or multiple resources, as displayed in written products, in this age group (e.g., Kuhn & Crowell, 2011;Schwarz, Neuman, Gil, & Ilya, 2003;Wissinger & De La Paz, 2016). In this research, it has been found that without extensive intervention, preferably in the form of collaborative dialogic argumentation about ill-structured problems or controversial issues (Bråten Muis, & Reznitskaya, 2017;Kuhn, 2015Kuhn, , 2018, students tend to disregard counterarguments and rebuttals and fail to integrate opposing arguments to reach a more balanced conclusion. This is consistent with other research focusing on the effects of students' preexisting positions or stances, to which we turn next.…”
Section: Prior Researchmentioning
confidence: 98%
“…Moreover, several researchers have studied argumentative reasoning about multiple perspectives or multiple resources, as displayed in written products, in this age group (e.g., Kuhn & Crowell, 2011;Schwarz, Neuman, Gil, & Ilya, 2003;Wissinger & De La Paz, 2016). In this research, it has been found that without extensive intervention, preferably in the form of collaborative dialogic argumentation about ill-structured problems or controversial issues (Bråten Muis, & Reznitskaya, 2017;Kuhn, 2015Kuhn, , 2018, students tend to disregard counterarguments and rebuttals and fail to integrate opposing arguments to reach a more balanced conclusion. This is consistent with other research focusing on the effects of students' preexisting positions or stances, to which we turn next.…”
Section: Prior Researchmentioning
confidence: 98%
“…The construct of the epistemic climate (Bendixen & Rule, 2004;Feucht, 2010a;Muis & Duffy, 2013) provides a broader context for the 3R-EC Framework. The educational model for personal epistemology (Feucht, 2010a) describes how the nature of knowledge and processes of knowing emerge from different epistemic entities in REFLECTION AND REFLEXIVITY classroom settings.…”
Section: Reflection and Personal Epistemologymentioning
confidence: 99%
“…Also in the same article by Bråten et al (2017) is evidence that supports the statements mentioned earlier by Haynes and Murris (2011) about teacher difficulty in implementing P4C. Although the article does not specifically reference P4C, it discusses facilitating classroom dialogue related to reasoning and argumentation, which is closely aligned to P4C.…”
Section: Beliefs and Values Of Teachers In Educationmentioning
confidence: 65%
“…Although the article does not specifically reference P4C, it discusses facilitating classroom dialogue related to reasoning and argumentation, which is closely aligned to P4C. Bråten et al (2017) say that this "poses a serious challenge for both new and experienced teachers" (p. 256), that more research is required to "explain why teachers still may find it challenging to teach deep understanding by engaging students in argumentation through inquiry dialogue" (p. 257), and that "engaging students in reasoned argumentation through classroom dialogue also poses new challenges to many teachers" (p. 265; cf. (Alverman & Hayes, 1989;Hammer & Schifter, 2001;Juzwik, Sherry, Caughlan, Heintz, & Borsheim-Black, 2012).…”
Section: Beliefs and Values Of Teachers In Educationmentioning
confidence: 99%
See 1 more Smart Citation